2007
DOI: 10.1111/j.1365-2389.2007.00949.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the extraction and quantification of amorphous silica in soils of forest and grassland ecosystems

Abstract: SummaryMany studies have highlighted the importance of the Amorphous Silica (ASi) pool to the overall mass balance in the biogeosphere. In order to advance our knowledge of measurements and quantification of this pool, it is necessary to compare the ability of different extractants to dissolve ASi in soils and to test methods developed in the aquatic sciences to soils systems. The methods used in this work included three acid extraction techniques (0.2 M NH 4 -oxalate, 0.1 M NH 4 -citrate and 0.5 M NH 4 -aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 140 publications
(150 citation statements)
references
References 29 publications
(66 reference statements)
10
140
0
Order By: Relevance
“…A generally higher solubility of the amorphous Si fraction as compared to the mineral phase makes it more easily available for biological (re-)cycling on shorter time scales . The reliability of the method has been shown for forested soils (Saccone et al, 2007), arable soils and wetland soils (Struyf and Conley, 2009). Approximately 30 mg of dried soil (<2 mm) was mixed in 40 ml of 0.094 M Na 2 CO 3 solution and digested for 5 h at 85 • C. A 1 ml aliquot was removed from the sample bottle after 3, 4 and 5 h and neutralized with 9 ml of 0.021 M HCl, before DSi determination (CSi d ) by the automated molybdate-blue method (Grasshoff et al, 1983).…”
Section: Alkali-extractionmentioning
confidence: 99%
“…A generally higher solubility of the amorphous Si fraction as compared to the mineral phase makes it more easily available for biological (re-)cycling on shorter time scales . The reliability of the method has been shown for forested soils (Saccone et al, 2007), arable soils and wetland soils (Struyf and Conley, 2009). Approximately 30 mg of dried soil (<2 mm) was mixed in 40 ml of 0.094 M Na 2 CO 3 solution and digested for 5 h at 85 • C. A 1 ml aliquot was removed from the sample bottle after 3, 4 and 5 h and neutralized with 9 ml of 0.021 M HCl, before DSi determination (CSi d ) by the automated molybdate-blue method (Grasshoff et al, 1983).…”
Section: Alkali-extractionmentioning
confidence: 99%
“…Melzer et al, 2012;Saccone et al, 2007;Sommer et al, 2013). The magnitude overlaps with Si Alk content attributed to tephra, the initial rapid dissolution of clay minerals and/or complete dissolution of nanocrystalline fractions in our experiments (Fig.…”
Section: Implications For Soil Scientistsmentioning
confidence: 77%
“…In addition, the sequential Na 2 CO 3 extraction is a rather simple method and the results show a high recovery of the biogenic Si fraction (Meunier et al, 2014;Saccone et al, 2007). The main advantage of the method is that a relatively large number of samples can be measured in a relatively short time span.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…These vegetation types are adapted to regularly flooding and thus have a character of a wetland. Moreover, grasses and sedges are known to contain significant amount of amorphous silica in their biomass (Saccone et al, 2007). In a recent study, Struyf and Conley (2009) have shown that especially these arctic wetlands are impressive storages of amorphous silica (ASi) that are either diatom frustules or phytoliths (Piperno, 1988).…”
Section: The Riparian Zone -A Hot Spot For Dsi River Loading In Arctimentioning
confidence: 99%